MANAGEMENT OF THE DERADICALIZATION PROGRAM FOR TERRORISM CONVICTS IN CLASS I CORRECTIONAL FACILITY SURABAYA - Rahfal, Muhammad Rizky Nabilla; Rahayu, Mulyani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The Correctional Institution (Lapas), as a facility for implementing punishment that deprives most of the inmates' rights, should properly consider rehabilitation programs for inmates, including deradicalization programs for terrorism convicts. Therefore, research was conducted on the management of deradicalization programs for terrorism convicts in Lapas to address issues related to deradicalization rehabilitation for these inmates. This research uses a qualitative method with a case study approach at Class I Correctional Institution in Surabaya. The results of the study show that the management of the deradicalization program for terrorism convicts in Lapas generally follows several stages: decision management, program governance, stakeholder engagement, change management, and benefits management. Furthermore, reducing radicalism among terrorism convicts is influenced by several key factors in the deradicalization program's implementation, including social relations, coping, identity, ideology, and action orientation. In the implementation of the deradicalization program, several obstacles were also encountered, including inmates who remain highly radicalized and thus reluctant to cooperate with the Lapas programs, a lack of human resources capable of conducting deradicalization rehabilitation, and sectoral egoism among various parties, which hinders the effective execution of the deradicalization program. Suggestions for improvement include adjusting the placement of high-risk terrorism convicts to Lapas that align with the revitalization of the penitentiary system, providing deradicalization programs and human resource training for the officers if terrorism convicts are present, and enhancing coordination among the program organizers to ensure that the deradicalization process runs as intended. Keywords : Correctional Institution; Terrorism Prisoners; Deradicalization; Program Management